2021
DOI: 10.1371/journal.pone.0250172
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination coverage estimation in Mexico in children under five years old: Trends and associated factors

Abstract: We aimed to estimate vaccination coverage and factors associated in completing schemes in children under 5 years old between 2000 and 2018. A secondary analysis was carried out on five national health surveys between 2000 and 2018 in Mexico. The sample was 53,898 children under 5 years old, where 30% of missing vaccination information was imputed using chained equations. During this period two basic vaccination schemes (CBS) were identified. For each doses and vaccines of both schemes and completed CBS, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…By 2012, data from the ENSANUT 2012 indicate that among children age 15 to 23 months, coverages were 96.7%, 68%, 88%, and 80% for BCG, pentavalent, pneumococcal conjugate (PCV), and rotavirus (RV), respectively, and 87% for measles, mumps, and rubella (MMR), and 0.2% of this age group was never vaccinated ( 11 ). In 2018, from the ENSANUT 2018, for children 12 to 23 months a coverage of 97.4% was estimated for BCG, and 92.1% for one dose of pentavalent vaccine ( 12 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By 2012, data from the ENSANUT 2012 indicate that among children age 15 to 23 months, coverages were 96.7%, 68%, 88%, and 80% for BCG, pentavalent, pneumococcal conjugate (PCV), and rotavirus (RV), respectively, and 87% for measles, mumps, and rubella (MMR), and 0.2% of this age group was never vaccinated ( 11 ). In 2018, from the ENSANUT 2018, for children 12 to 23 months a coverage of 97.4% was estimated for BCG, and 92.1% for one dose of pentavalent vaccine ( 12 ).…”
mentioning
confidence: 99%
“…However, more recent analyses suggest a reversal of trend. An analysis of the ENSANUT from 2000 to 2018 identified a negative trend in vaccination coverage for children under 5 in Mexico and found that the probability of incomplete vaccination was related to socioeconomic and geographic factors ( 12 ). A similar analysis using only the 2012 and 2018-100k rounds of the ENSANUT found similar results, with decreasing coverage for specific vaccines and overall coverage of the complete scheme around 50% ( 13 ).…”
mentioning
confidence: 99%